The Effect of Work Environment and Supervisors' Support on Employee Retention in Indonesian Sharia Bank Palopo City - Rohimah, Innayatul; Saharuddin, Saharuddin; Usman, Halim (PT. EQUATOR SINAR AKADEMIA, 2026)
Source Power man is asset strategically decisive​ sustainability and excellence competitive organizations , including in industry Islamic banking . Bank Syariah Indonesia, Palopo City Keep going make an effort maintain power Work professional through creation environment conducive work​ as well as strengthening support leadership . Research This aim For analyze influence environment work and support superior to retention employees at Bank Syariah Indonesia in Palopo City . Research use approach quantitative with method survey through distribution questionnaire to all over population consisting of of 50 employees . Data processed use analysis multiple linear regression with SPSS software. Environment Work influential positive However No significant to retention employees . On the other hand , support superior influential positive and significant to retention employees . In simultaneous , both variables influential significant to retention employee with mark coefficient determination of 0.960, which means 96% of the variation retention employee can explained by the environment work and support superiors , while 4% is influenced by other variables outside the model. Findings This confirm that support superior is more factors​ dominant in increase retention employees at Bank Syariah Indonesia in Palopo City . Research This give implications for management For strengthening retention strategies through improvement quality connection Work between leaders and employees .